2006
DOI: 10.1021/ma060516o
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Solid-State Structures of Single-Site and Ziegler−Natta Linear Low-Density Polyethylenes As Revealed by Molecular Dynamics Simulation

Abstract: Molecular dynamics (MD) simulations were carried out to study the solid-state structures of singlesite (ss) and Ziegler-Natta (ZN) linear low-density polyethylenes (LLDPE) at a temperature slightly below their melting temperatures. The two bulk state models, used to represent the polymers, possessed the same average branch content (10 hexyl branches per 1000 backbone carbons) but with different degrees of interchain branch distribution homogeneity. Both models were first equilibrated at 463 K (i.e., 190 °C) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
(63 reference statements)
5
18
0
Order By: Relevance
“…This observation is similar to that observed by Wang et al in their experiments. This trend also appears to be consistent with the observations of Zhang et al from MD simulations, but probably for very different reasons, since the distributions of branch points in the current work were determined by thermodynamic considerations and not fixed by a certain topological distribution and short time kinetics. The observed trends are at odds with the lattice simulation results of Mattice et al and with many proposed interpretations of experimental data.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is similar to that observed by Wang et al in their experiments. This trend also appears to be consistent with the observations of Zhang et al from MD simulations, but probably for very different reasons, since the distributions of branch points in the current work were determined by thermodynamic considerations and not fixed by a certain topological distribution and short time kinetics. The observed trends are at odds with the lattice simulation results of Mattice et al and with many proposed interpretations of experimental data.…”
Section: Discussionsupporting
confidence: 92%
“…However, lattice models are limited in their ability to represent accurately the conformers and packing interactions of real systems over distances of only a few bonds, and the model of Mattice and co-workers did not capture the difference in density between the crystalline and noncrystalline regions. Zhang et al 34 subsequently carried out molecular dynamics (MD) simulations of branched polyethylenes using a united atom (UA) model, with chains constructed to mimic material obtained using either ss or ZN catalysts. Upon quenching to 375 K, they observed the formation of small crystallites in both cases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In all these works, the characteristic general trends observed experimentally in SCB polyolefins are noted, such as rejection to the amorphous regions of branches longer than methyl, and a decrease in crystal size and melting temperatures with SCB content [121-123, 243, 244, 335-337].Very few simulations can be found to study the effects of SCB on polymer crystallization from the melt. Choi et al examined solid-state structures formed in the early stage of crystallization of different homogeneous and heterogeneous LLDPE models by means of MD simulations using the DREIDING FF [338,339]. These simulation results show that for homogenously branched systems, SCBs are distributed in both the interphase and the amorphous regions.…”
Section: Crystallization From the Meltmentioning
confidence: 99%
“…Ramos et al [43] reported that the lamellar thickening processes of the branched polyethylene samples were impeded when compared with that of the linear polyethylene system. Choi et al [44,45,46] investigated the branch effects on the structure of linear low-density polyethylene, and identified a critical branch content (38.5 SCB/1000 backbone carbons) where the branch length began to influence the order parameter. Rutledge et al [47] observed that the interfacial region’s thicknesses of linear polyethylene systems were bigger than those found for branched systems.…”
Section: Introductionmentioning
confidence: 99%